PERGURUAN ISLAM REPUBLIK INDONESIA YOGYAKARTA DAN TRANSMISI PENGETAHUAN GERAKAN AHMADIYAH INDONESIA - Husen Hasan Basri (Badan Litbang dan Diklat Kementerian Agama RI, 2014)
There are pros and cons to the existence of the Islamic University of Indonesia (PIRI). Some perceive it as a seeding site of Indonesian Ahmadiyah Movement (GAI) ideas and values. PIRI is alleged to have carried out knowledge transmission for GAI. But for some other, PIRI is a foundation organizing merely educational activities without any affi liation to GAI, especially with regard to such knowledge transmission. Through a qualitative research approach, it is found that PIRI was born from an idea of GAI founders that the spirit of GAI underlies the PIRI education activities. Most of the principals at PIRI schools indeed come from GAI. However, most of the teachers come from a variety of socio-religious backgrounds, and the students are from the community that has never been the followers of GAI. PIRI adopts curriculum produced by the Ministry of Education and Culture for secular subjects and that produced by the Ministry of Religious Affairs for Islamic as well as their PIRI (Ahmadiya)-specifi c subject matters. In conclusion, there is historical and spiritual relationship between PIRI and GAI and not organizational relationship. Although there are attempts of GAI knowledge transmission in PIRI, but education in PIRI schools is more oriented to their educational goals of integrating to social changes in the community, and conformity to the Indonesian national education system.